The Instructor's Guide for the SOS-REACH (Suspected Observable Senior Resident Empowerment Action Checklist) and SREA-21: Tools for Evaluating Senior Resident Empowerment During Family-Centered Rounds - Michael Weisgerber; Heather Toth; Carri Brewer; Dawn Bragg; Natlie Metzig; Karen Marcdante; Deborah Simpson (Association of American Medical Colleges, 2011)
Abstract Introduction Being a senior resident on the inpatient ward team is one of the most important and challenging roles a resident assumes during training. While the medical education literature has identified principles that are important for student and resident learning, less attention has been given to the unique role of the senior resident, particularly in the setting of inpatient rounds. Many important senior resident roles and competencies can be developed and demonstrated during inpatient rounds, particularly those where the patient and family interacts with members of the care team. We therefore developed the term senior resident empowerment actions (SREAs) to represent specific behaviors that empower senior residents as leaders and teachers during family-centered rounds. The Suspected Observable Senior Resident Empowerment Action Checklist (SOS-REACH) and the abbreviated version titled the Senior Resident Empowerment Action Checklist-21 (SREA-21) was developed to assess these behaviors. Methods The SOS-REACH is a 47-item measure divided into five domains based on distinct elements of the patient encounter: leadership, teaching, family interactions, assessment/plan formulation, and efficiency. The SREA-21 contains an abbreviated version and contains 21 items. Both tools may be used to conduct observations of and provide feedback to senior residents and faculty during family-centered rounds. Results The SOS-REACH (from which the SREA-21 is derived) was used to observe 23 patient rounds with four to nine patients per round during a 1 year period among three trained observers for a total of 311 individual patient observations. The reliability between the observers as determined by the intraclass correlation coefficient was 0.84. Content validity of the SREAs chosen and placed on the SOS-REACH was established with a systematic process for identifying SREAS using three sources: literature review for behaviors successful in other learners (medical students, interns, and business people), structured group interviews of residents and faculty, and findings of the trained observers during the pilot phase of the study. Discussion The SOS-REACH and the abbreviated SREA-21 tools incorporate these results to provide an evidence-based approach to teaching, promoting, and evaluating the use of SREAs at any academic institution engaging in family-centered rounds.